Trace Element Analysis in Ground-Water of Bhopal - Kataria, H.C.; Dubey, K.S. (Asian Journal of Chemistry, 2010)
The aim of the present study is to assess the trace elements in groundwater in year 1993-94 by atomic absorption spectrophotometer. Cu andZn trace elements ranged from 0.010–0.480 and 0.066–1.850 ppm at differentsampling stations of Bhopal City.